2016
DOI: 10.1080/1061186x.2016.1236112
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in targeting mTOR signaling pathway using small molecule inhibitors

Abstract: Targeted-based cancer therapy (TBCT) or personalized medicine is one of the main treatment modalities for cancer that has been developed to decrease the undesirable effects of chemotherapy. Targeted therapy inhibits the growth of tumor cells by interrupting with particular molecules required for tumorigenesis and proliferation of tumor cells rather than interfering with dividing normal cells. Therefore, targeted therapies are anticipated to be more efficient than former tumor treatment agents with minimal side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…While inhibition of mTOR alone in a mouse model of colorectal tumorigenesis failed to inhibit translation of myc , a small molecule inhibitor of eIF4A, silvestrol, effectively reduced myc translation, inhibiting tumor growth (Wiegering et al, 2015 ). Multiple mTOR and mTORC1/2 kinase inhibitors are currently approved for clinical use, and there is a significant focus on targeting many members of these signaling pathways (Polivka and Janku, 2014 ; Roohi and Hojjat-Farsangi, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…While inhibition of mTOR alone in a mouse model of colorectal tumorigenesis failed to inhibit translation of myc , a small molecule inhibitor of eIF4A, silvestrol, effectively reduced myc translation, inhibiting tumor growth (Wiegering et al, 2015 ). Multiple mTOR and mTORC1/2 kinase inhibitors are currently approved for clinical use, and there is a significant focus on targeting many members of these signaling pathways (Polivka and Janku, 2014 ; Roohi and Hojjat-Farsangi, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Torin1 has slower off‐binding kinetics than other mTOR inhibitors in mammalian cell lines, possibly due to conformational change induction in the kinase that is energetically more difficult to recover from leading to a more pronounced and longer inhibition of the TORC1 pathway (Liu et al ., ). AZD8055 is an ATP‐competitive inhibitor of mTOR and all PI3K class I isoforms noted to inhibit the mTORC1 and mTORC2 substrate phosphorylation (Roohi & Hojjat‐Farsangi, ). These drugs were used to inhibit TOR activity in plants where rapamycin treatment is not highly effective (Zhang et al ., ; Montane & Menand, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in rats with appropriate treatment after cerebral ischemia-reperfusion, there was no significant difference in the expression of mTOR signaling pathway related genes in hippocampus when compared with healthy rats (P>0.05), and its cognitive function was not significantly decreased, suggesting the decline of cognitive function in rats after cerebral ischemia-reperfusion may be generated through the mTOR signaling pathway. Further studies on the mTOR signaling pathway have found that the mTOR signaling pathway participates in many physiological and biochemical reactions in cells ( 22 , 23 ). For example, previous results have shown that the mTOR signaling pathway can sense the changes of intracellular energy as well as intracellular nutrients, thus regulating many physiological reactions in cells including gene transcription, translation, ribosome generation and amino acid intake.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous results have shown that the mTOR signaling pathway can sense the changes of intracellular energy as well as intracellular nutrients, thus regulating many physiological reactions in cells including gene transcription, translation, ribosome generation and amino acid intake. Furthermore, the mTOR signaling pathway plays an important role in the regulation of multiple neural processes, such as formation and development of the brain, formation and maturation of synapses and neural cell proliferation ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%